Oral health beliefs and oral hygiene behaviours among parents of urban Alaska Native children. Issue 1 (1st January 2019) - Hiratsuka, Vanessa Y.; Robinson, Jamuir M.; Greenlee, Robert; Refaat, Amany
ABSTRACT: American Indian/Alaska Native (AI/AN) children have a prevalence rate of early childhood caries 5 times that of the overall US population. Oral hygiene and oral health beliefs have not been described among AI/AN parents. This study explored constructs of the health belief model informing oral health beliefs and oral hygiene behaviours of parents of AI/AN children ages 0-6 years. The study aimed to determine the toothbrushing behaviour in parents of AI/AN childrenand the relationship between parent oral health beliefs and toothbrushing frequency. A cross-sectional survey which included the Oral Hygiene Scale, Oral Health Belief Questionnaire and the Early Childhood Oral Health Impact Scale was administered to a convenience sample of parents of AI/AN children 71 months or younger attending outpatient paediatric primary care appointments (N=100). Analyses were conducted to determine parent toothbrushing and the relationship between parent health beliefs and child toothbrushing. The odds of regular child toothbrushing were 49.10 times higher when the parent brushed their own teeth regularly (confidence interval (CI)=11.46–188.14; p<0.001). Parental toothbrushing had a strong positive association with the belief that oral health is as important as physical health. This research endorses parent-focused toothbrushing interventions to reduce AI/AN early childhood caries rates.